2017
DOI: 10.1001/jamainternmed.2016.8245
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Contagion Through Social Networks to Explain and Predict Gunshot Violence in Chicago, 2006 to 2014

Abstract: IMPORTANCEEvery day in the United States, more than 200 people are murdered or assaulted with a firearm. Little research has considered the role of interpersonal ties in the pathways through which gun violence spreads.OBJECTIVE To evaluate the extent to which the people who will become subjects of gun violence can be predicted by modeling gun violence as an epidemic that is transmitted between individuals through social interactions.DESIGN, SETTING, AND PARTICIPANTS This study was an epidemiological analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
115
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(130 citation statements)
references
References 62 publications
5
115
0
Order By: Relevance
“…Violence is clearly a health problem because victims experience physical injuries, premature death, and adverse health behaviors (7,19,73,79). Violence is also clustered in time and space (13,40). Exposure to violence may lead to the intergenerational transmission of violence, or a "cycle of violence" (87), where childhood experiences such as abuse and neglect can lead to later victimization, perpetration (2), or self-harm (30,68).…”
Section: Introductionmentioning
confidence: 99%
“…Violence is clearly a health problem because victims experience physical injuries, premature death, and adverse health behaviors (7,19,73,79). Violence is also clustered in time and space (13,40). Exposure to violence may lead to the intergenerational transmission of violence, or a "cycle of violence" (87), where childhood experiences such as abuse and neglect can lead to later victimization, perpetration (2), or self-harm (30,68).…”
Section: Introductionmentioning
confidence: 99%
“…52 Physical and social proximity to higher risk individuals—especially those involved in gun violence—has been shown to increase rates of co-offending (being arrested for the same offense), amplifying risky behaviors, and being more predictive of victimization than demographic information alone. 6,53–55 For these reasons, two essential threads to be assessed are level of participation in gangs and in illegal activities, and incarceration history. In consideration of this fact, these factors’ placement in Category A (elevated-risk indicators) is justified.…”
Section: Discussionmentioning
confidence: 99%
“…1 Many of these patients suffer a subsequent violent injury, with recidivism rates as high as 58%. 3–6 Hospital-based violence intervention programs (HVIP) have been created to reduce injury recidivism among patients at risk of re-injury. However, to our knowledge no formal methods of assessing patient’s risk of re-injury have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…As noted, high-risk individuals tend to be central in the social networks of those involved in crime (e.g., Green, Horel, and Papachristos, 2017;Papachristos, Wildeman, and Roberto, 2015). Here, being central typically relates to "degree centrality"-having comparatively large numbers of links to others involved in criminal activity, either directly or indirectly (for subjects who link to others who, in turn, are linked to many others).…”
Section: Identifying Those At High Risk For Involvement In Violencementioning
confidence: 99%
“…Research has shown that subjects who have numbers of co-arrest links that make them part of social networks with members suffering lots of violent attacks are likely to be parties of violence themselves (Green, Horel, and Papachristos, 2017;Papachristos, Wildeman, and Roberto, 2015).…”
Section: Identifying Those At High Risk For Involvement In Violencementioning
confidence: 99%